AAV-Mediated Astrocyte-Specific Gene Expression under Human ALDH1L1 Promoter in Mouse Thalamus - Koh, Wuhyun; Park, Yongmin Mason; Lee, Seung Eun; Lee, C. Justin (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2017)
Adeno-associated virus (AAV)-mediated gene delivery has been proposed to be an essential tool of gene therapy for various brain diseases. Among several cell types in the brain, astrocyte has become a promising therapeutic target for brain diseases, as more and more contribution of astrocytes in pathophysiology has been revealed. Until now, genetically targeting astrocytes has been possible by utilizing the glial fibrillary acidic protein (GFAP) promoter. In some brain areas including thalamus, however, the GFAP expression in astrocytes is reported to be low, making it difficult to genetically target astrocytes using GFAP promoter. To study the function of astrocytes in thalamus, which serves as a relay station, there is a great need for identifying an alternative astrocyte-specific promoter in thalamus. Recently, a new astrocyte-specific promoter of ALDH1L1 has been identified. However, it has not been examined in thalamus. Here we developed and characterized an AAV vector expressing Cre recombinase under the human ALDH1L1 promoter, AAV-hALDH1L1-Cre. To test the cell-type specific expression of AAV-hALDH1L1-Cre, AAV virus was injected into several brain regions of Ai14 (RCL-tdTomato) mouse, which reports Cre activity by tdTomato expression. In thalamus, we observed that tdTomato was found mostly in astrocytes (91.71%), with minimal occurrence in neurons (2.67%). In contrast, tdTomato signal was observed in both neurons and astrocytes of the amygdala (neuron: 68.13%, astrocyte: 28.35%) and hippocampus (neuron: 76.25%, astrocyte: 18.00%), which is consistent with the previous report showing neuronal gene expression under rat ALDH1L1 promoter. Unexpectedly, tdTomato was found mostly in neurons (91.98%) with minimal occurrence in astrocytes (6.66%) of the medial prefrontal cortex. In conclusion, hALDH1L1 promoter shows astrocyte-specificity in thalamus and may prove to be useful for targeting thalamic astrocytes in mouse.
Keywords: FIBRILLARY ACIDIC PROTEIN; NERVOUS-SYSTEM; BRAIN; DELIVERY; VECTORS; NEURONS; CELLS; MICE; GFAP